The Origins of Viking Age Dogs in Luistari, Eura, Finland - Nordfors, Ulla; Danielisová, Alžběta; Etu‐Sihvola, Heli; Ackerman, Lukáš; Mannermaa, Kristiina; Arppe, Laura (Wiley, 2025)
We used stable (δ18O) and radiogenic (87Sr/86Sr) isotopic proxies to investigate the origins of dogs (Canis familiaris) buried in Viking Age graves at Luistari, Finland. While all 13 dogs exhibited oxygen isotope values compatible with local surface waters, 87Sr/86Sr ratios for two of the four dogs analyzed (graves 289 and 480) were compatible with a likely origin in southern Scandinavia. The findings align with previous evidence of the mobility of Viking Age dogs. The results highlight the importance of dogs in trade, exchange and social networks between communities in southwestern Finland and the Baltic Sea coastline during the Viking Age.